Reports of Judgments, Advisory Opinions and Orders: Alleged Violations of the 1955 Treaty of Amity, Economic Relations, and Consular Rights (Islamic Republic of Iran v. United States of America) - International Court of Justice (United Nations, 2022)
This series contains the decisions of the Court in both the English and French texts. Each decision is published as soon as possible after it has been given, in an unbound fascicle, which is sold separately. To allow for binding, a continuous system of pagination is adopted for all the fascicles of any one year. Early each year an analytical index is published of the previous year's decisions; this may also be purchased separately. A binder is available for those who have obtained the separate fascicles and index at the time of their publication. The collected decisions, with index, for each year, may also be obtained ready bound in one volume.